A Passion for Excellence : The Leadership Difference - Peters, Tom, 1929- and Austin, Nancy (London Profile Books Ltd., 2007)
The authors divulge the three secrets of long-term excellence: superior customer or client service, innovation, and full use of the abilities of every company employee. But the one element linking these three is leadership, and the heart and soul of the concept is Management by Wandering About.
Include Index.
Keywords: United States -- Industrial Management -- Leadership